ANALISIS KELENGKAPAN LABORATORIUM KIMIA DI SMA NEGERI 3 SORONG - VINA N VAN HARLING; Stefany Margareta Martono (LPPM Politeknik Saint Paul Sorong, 2021)
Scientific work is in the form of practicum activities that take place in a laboratory equipped with supporting tools and materials. Practical activities in the laboratory in the learning process can increase students' knowledge to solve problems using the theory that has been given systematically. The purpose of this study was to analyze the completeness of the chemistry laboratory at SMA Negeri 3 Sorong City. Laboratory analysis based on standard facilities and Permendiknas RI No. 24 of 2007. The method used in this research is the descriptive method with a quantitative approach. The school subjects used in this study were SMA Negeri 3 Sorong. The results of the analysis of the completeness of the chemical laboratory at SMA Negeri 3 Sorong City showed that 87.5% of the furniture used for practicum was available in the laboratory, while the suitability of the equipment used was 51.42%. For consumables stored in the laboratory as a whole by existing standards (100%), and as much as 80% of other available equipment, so the analysis results show that the chemical laboratory equipment owned by SMA Negeri 3 Sorong is by the standard of facilities. and laboratory infrastructure in this case Permendiknas RI No. 24 of 2007.